Investigation and preparation of CeO2-TiO2/FA (fly ash) SCR catalyst. Issue 181 (13th June 2017) - Ren, Xiufeng; Hai, Chunxi; Li, Xiang; Shen, Yue; Zeng, Jinbo; Zhou, Yuan; Chen, Yunfa
ABSTRACT: CeO2 -TiO2 /FA catalysts with the selective catalytic reduction (SCR), using industrial solid waste-Fly Ash (FA) as the supporter was prepared by sol-gel and insuccation methods. Ammonia was used as reducing gas to detect the catalytic performance of as-prepared catalyst. Surface structure and catalytic properties of the catalyst were characterized by using BET, XRD, SEM and denitrification tests, respectively. It was confirmed that the loading of CeO2 and TiO2 on FA supporter led to the increased the specific surface area of catalysts, which resulted in the enhanced catalytic performance toward removing NOx. The NOx conversion over this catalyst can reach 95.3%.